Global Path Planning For Solar-Powered Uav - Wahab, Abdul Aniq Aqil Abd (Universiti Sains Malaysia, 2021)
The unmanned aerial vehicle (UAV) is widely use nowadays due to its functionality and capable of undergoes many types of mission. The solar-powered unmanned aerial vehicle (SUAV) is preferable over conventional UAV as it provide high-level of sustainability and endurance. This solar-powered UAV need comprehensive mission planning to make sure that it has enough power to sustain a perpetual flight. In this research, a simulation using MATLAB to test various optimal flight path pattern for UAV is configurated and analyzed, then a best flight pattern to sustain a continuous mission will be selected. The study of daylight duration and solar irradiance on earth is included in this research to plan a best flight path in term of endurance. The simulated solar-powered UAV is maintained at 100 m above ground level and fly at minimum cruise velocity throughout the mission. The simulation is carried out by creating a hexagonal discrete global grid over the 0.03% of earth map and testing as many as possible path in each hexagon cell. The path is pre-determined, and the hexagon cell is generated by declaring the points on side of hexagon shape based on latitude-longitude coordinates system of earth. The path is further analyzed to find best path for UAV in term of least distance travelled and longest flight time or perpetual flight with most SOC state. Overall, the horizontal systematic path pattern emerges as the best systematic path pattern as for the horizontal path pattern the percentage of usage is the highest which at 88% compared to diagonal path pattern which only at 12%.